Evaluation of housing construction strategies in China using fuzzy‐logic system - Perng, Yeng‐Horng; Hsueh, Sung‐Lin; Yan, Min‐Ren (International Journal of Strategic Property Management, 2010)
There is a large demand for and a large profit potential in the Chinese housing market. However, foreign investors still suffer high risk because they are unfamiliar with the complexities of this enormous market. This paper presents the issues associated with housing sales in the People’s Republic of China and the applications of Fuzzy Logic and Delphi Method to the prediction of sales performance in China’s housing. Furthermore, the study presents the concept of an AND/OR logic gate based model, so that expert knowledge can be converted through computation into the needed rules for decision making related to housing sales performance prediction. The logic gate model is useful for ‘if‐then’ rule analysis, monitoring during the model building and amendment process, and in model maintenance in the later stages of its application. The aim of the described model is to provide a computer‐based decision support tool for foreign investors and contractors in evaluating beforehand the business feasibility of entering the Chinese housing market. First Published online: 18 Oct 2010